2021
DOI: 10.1007/s00018-021-03979-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a: the bad guy in age-related vascular diseases

Abstract: The age-related vasculature alteration is the prominent risk factor for vascular diseases (VD), namely, atherosclerosis, abdominal aortic aneurysm, vascular calcification (VC) and pulmonary arterial hypertension (PAH). The chronic sterile low-grade inflammation state, alias inflammaging, characterizes elderly people and participates in VD development. MicroRNA34-a (miR-34a) is emerging as an important mediator of inflammaging and VD. miR-34a increases with aging in vessels and induces senescence and the acquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 209 publications
(351 reference statements)
0
34
0
Order By: Relevance
“…A recent review generalized the role of miR-34a in vascular aging and senescence, demonstrating that miR-34a promoted vascular aging through targeting SIRT1 or regulating vascular cell adhesion protein1 and intercellular adhesion molecule 1 at least partially (55). More importantly, activation of FOXO3 promoted stress resistance in differentiated human vascular endothelial and smooth muscle cells which related to cellular aging (56).…”
Section: Mir-34a and Cardiovascular Senescencementioning
confidence: 99%
“…A recent review generalized the role of miR-34a in vascular aging and senescence, demonstrating that miR-34a promoted vascular aging through targeting SIRT1 or regulating vascular cell adhesion protein1 and intercellular adhesion molecule 1 at least partially (55). More importantly, activation of FOXO3 promoted stress resistance in differentiated human vascular endothelial and smooth muscle cells which related to cellular aging (56).…”
Section: Mir-34a and Cardiovascular Senescencementioning
confidence: 99%
“…It is becoming a vital mediator of inflammation and VD. This is because microRNA34a expression increases with vascular ageing, and it causes VSMCs and ECs to acquire the SASP [ 109 ]. It has been reported that senescent cells have this specific secretory phenotype that alters the homeostasis of surrounding tissues and the environment.…”
Section: Senescence Of Endothelial Cellsmentioning
confidence: 99%
“…Since oxidative stress, hypoxia, and VSMC proliferation play a critical role in AVF maturation/failure, these miRNAs might play an important role. The levels of miR-34a-5p, associated with atherosclerosis and miR-34a-5p, play a crucial role in inflammatory pathology [ 67 ] and various studies [ 68 , 69 ] have discussed miR-34a-5p, which was found to be inhibited in this study, as a potential therapeutic target in cardiovascular disease. miR-205-5p, which was found to be activated in this study, suppresses the proliferation of pulmonary VSMCs [ 70 ], whereas miR-153, which was found to be inhibited in this study, attenuates hypoxia-induced excessive proliferation and migration of pulmonary arterial SMCs [ 71 ].…”
Section: Discussionmentioning
confidence: 84%